PENGEMBANGAN PERANGKAT PEMBELAJARAN BERBASIS INKUIRI DENGAN MODEL LEARNING CYCLE 7E UNTUK MENINGKATKAN HASIL BELAJAR FISIKA TOPIK CAHAYA - Fitriyah, Ida (Universitas Negeri Surabaya, 2013)
This is the research of development that intends to develop learning purchase based on inquiry by 7E learning cycle model in the light topic included syllabus, lesson plan, students book, students worksheet, and assesment sheet. This research is done by using three steps, they are Development of learning instrument with Kemp model, validation of instrument and field experiment by one group pretest-posttest design, which is done in SMPN 1 Tuban. The result of this research is 1) Learning instrument based on inquiry by 7E learning cycle models is valid for being done in learning: a) The result of instrumen validity refers to learning instrument in good category and it can be used in teaching learning process ; b) The difficulty level of instrument is low a nd easy is understood by student; c) Readablety of instrumen is high and the materials easy is understood by students; 2) The learning instument is effective to use in learning process; a) the value of cognitive test, performence test and affective test refer to the improvement with high category; b) The students give a positive response to the learning process; 3) The learning instrument which has been developed is practical to use in learning process; a) The lesson plan that used is in a good category; b) the hig est procentage of three student activity are analysis the result of experiment, doing experiment / observation, and discussion/question - answer. The conclusion of the research analising is the learning purchase which has been developed based on inquiry by 7E learning cycle model in the light topic have fullfiled validity, effectify and practical to use, so itis proper to use in learning process.Penelitian ini merupakan penelitian pengembangan yang bertujuan mengembangkan perangkat pembelajaran berbasis inkuiri dengan model learning cycle 7E topik Cahaya, meliputi Silabus, RPP, Materi ajar, LKS dan Lembar Penilaian. Penelitian ini dilaksanakan di SMPN 1 Tuban melalui tiga tahap, yaitu pengembangan perangkat dengan model Kemp, validasi perangkat, dan ujicoba lapangan dengan rancangan one group pretest-posttest. Hasil dari penelitian ini adalah 1) Perangkat Pembelajaran berbasis inkuiri dengan model Learning Cycle 7E valid untuk digunakan dalam pembelajaran; a) Hasil validasi perangkat menunjukkan perangkat pembelajaran yang dikembangkan berkategori baik dan dapat diterapkan dalam kegiatan belajar mengajar; b) Tingkat kesulitan perangkat yang dikembangkan rendah dan mudah dipahami siswa; c) Keterbacaan perangkat tinggi dan materi mudah dipahami; 2) Perangkat pembelajaran efektif digunakan dalam proses pembelajaran; a) Hasil belajar kognitif produk, proses, psikomotor, dan afektif menunjukkan peningkatan dengan kategori tinggi; b) Siswa memberikan respon positif terhadap perangkat pembelajaran yang dikembangkan. 3) Perangkat pembelajaran yang dikembangkan praktis digunakan dalam pembelajaran; a) keterlaksanaan RPP dalam kategori baik; b) Aktivitas siswa yang memiliki persentase tiga terbesar adalah menganalisis hasil percobaan, melakukan percobaan/ pengamatan, dan diskusi/tanya jawab. Penelitian ini berkesimpulan bahwa Perangkat Pembelajaran berbasis inkuiri dengan model Learning Cycle 7E topik Cahaya yang telah dikembangkan memenuhi unsur kevalidan, keefektifan dan kepraktisan, sehingga layak diimplementasikan dalam pembelajaran.